Sleep disturbance and quality of life among university freshmen in Qinghai–Tibet Plateau of China - Zhang, Tiantian; Lu, Li; Ren, Yan-Ming; Liu, Yu-Ying; Hynek, Kamila Angelika; Gao, Jie; Chen, Hong-Ru; Shen, Hong-Yi; Gai, Xiang-Yun; Dang, Zhan-Cui; Liu, Shou (Frontiers in Psychiatry, 2022)
Purpose: University freshmen are particularly vulnerable as they are undergoing the transition from high school to university with a range of changes. Sleep problems among this group in the Qinghai-Tibet Plateau of China were barely studied. This study aimed to explore sleep disturbance, and its association with Quality of life (QoL) and demographic and clinical characteristics among university freshman in Qinghai-Tibet Plateau, China. Methods: A multistage stratified cluster sampling method was performed to recruit student participants with a structured questionnaire to collect sociodemographic and clinical characteristics, and lifestyle behaviors. Sleep disturbance including three aspects of sleep disturbance (i.e., difficulty initiating sleep (DIS), difficulty maintaining sleep (DMS), early morning awakening (EMA)) was assessed using standardized measurement. Multiple logistic regression models were applied to analyze the data. Results: Among included 2769 freshmen, the prevalence of sleep disturbance was 14.8% (95% CI: 14.2%-15.5%), and corresponding prevalence of DIS, DMS and EMA were 8.2% (95% CI: 7.7%-8.7%), 8.3% (95% CI: 7.8%-8.8%) and 4.2% (95% CI: 3.8%-4.6%), respectively. Freshmen with sleeping disturbance had significantly lower QoL in physical (F (1, 2769) =60.23, p<0.001), psychological (F (1, 2769) =46.18, p<0.001), social (F (1, 2769) =23.04, p<0.001) and environment (F (1, 2769) =6.07, p=0.01) domains. Multiple logistic regression analyses revealed that having breakfast less than 5 times a week (less than 3 times, OR=1.79, 95% CI: 1.34-2.40; 3-5 times, OR=1.40, 95% CI: 1.09-1.79), self-perceived severe Internet dependence (OR=1.71, 95% CI: 1.11-2.65), self-perceived poor health status (OR=3.44, 95% CI: 2.06-5.74), high academic stress (OR=1.42, 95% CI: 1.13-1.78), poor relationship with classmates (OR=3.44, 95% CI: 1.53-7.71) and severe ADHD symptoms (OR=1.08, 95% CI: 1.05-1.12) were positively associated with sleeping disturbance. Conclusions: Sleep disturbance was common among freshmen and is associated with poorer QoL. Prevention and intervention strategies should be developed and implemented especially among the vulnerable University freshman groups.